Implementasi Budaya Mutu pada Madrasah Diniyah Takmiliyah: Integrasi Nilai-Nilai Al-Qur'an dan Filosofi Total Quality Management (TQM) - Hadrian Nur; Dakir Dakir; Triwid Syafarotun Najah (Indo Publishing, 2026)
This study aims to analyze the concept of quality culture in Madrasah Diniyah Takmiliyah (MDT), examine the quality values ​​contained in the Qur'an, explore the relevance of Total Quality Management (TQM) principles in Islamic education, and formulate a quality culture model that integrates the Qur'anic perspective and TQM philosophy. The study uses a qualitative approach with a library research method that utilizes various sources in the form of the Qur'an, tafsir books, books, and scientific articles relevant to quality culture, TQM, and Islamic education. Data are analyzed using content analysis and conceptual synthesis techniques to find the relationship between Qur'anic values ​​and quality management principles. The results show that quality culture in MDT is an organizational culture based on Islamic values ​​and oriented towards continuous improvement in academic, spiritual, moral, and social aspects. The Qur'an provides a normative foundation through the concepts of ihsan, itqan, amanah, syura, muhasabah, and islah, which align with the main principles of TQM, such as excellence, quality assurance, accountability, participation, evaluation, and continuous improvement. Based on these findings, this study formulates the Qur'anic-TQM Quality Culture model as a framework for MDT management that integrates spiritual, cultural, and managerial dimensions. This model represents a novel research value because it offers a quality culture approach that is not only oriented toward improving institutional quality but also toward strengthening the character and spirituality of students. Therefore, it can be an alternative for effective, sustainable quality development that aligns with the characteristics of Madrasah Diniyah Takmiliyah.